The illegal immigrants in Sabah: Why do they come back? - Wan Shawaluddin Wan Hassan; Marja Azlima Omar; Ramli Dollah (Penerbit UM, 2010)
The numbers of illegal immigrants from neighbouring countries of the Philippines and Indonesia is said to have reached an alarming figure. Recent statistics estimates that the number of immigrants in the country is approximately half a million. Such noticeable presence of the immigrants has been a major concern to many. Although, the immigrants may have profoundly contributed to the economic development of Sabah, their contribution is not without its cost. While providing cheap labour to timber, construction, plantation and domestic sectors, they are also seen as a threat to the society as a significant numbers of them are also involved in criminal activities. In order to negate negative effects, the government responded by taking several measures inter alia canning and deportation. Nonetheless, those measures failed to completely hinder them from coming back. Based on interviews and observations carried out in Kota Kinabalu, Sandakan, Tawau, Semporna, Kunak and Lahad Datu, this paper seeks to verify the reasons of their returning. This paper concludes that the immigrants will continue to come back regardless of whatever measures taken by the government for as long as job opportunities are abundantly available in Sabah. In addition, the availability of ‘shelter’ provided by their relatives who are locals is also a crucial factor.